The (dis) illusion of autonomy: an approach to work in the UBER company in the Metropolitan Area of Buenos Aires - Diana Menéndez, Nicolás (2023)
Introduction: The platform economy has invaded social relations in every way. Products of the information revolution, artificial intelligence and big data, the platforms constitute a sign of the times that crosses and deepens the set of pre-existing mercantile relations while commodifying a series of activities that, until their arrival, were outside to data extractive logic. The consequences of this irruption for the world of work are multiple and profound. Objectives: Here we propose to analyze the control practices and working conditions at UBER, the company that constitutes a paradigm of the new work management logics through digital platforms. Methodology: The study is qualitative in nature, based on ten in-depth interviews with UBER drivers during the years 2019 and 2020, in which, among other dimensions, working conditions, control mechanisms and meanings of work were investigated. Likewise, periodic monitoring of two driver and passenger forums was carried out. Results: Throughout the writing, a multiplicity of daily practices developed by the Uber company to influence the behavior and control the activity of drivers is observed. The platform's capacity to algorithmically manage work in a massive and personalized way is verified, with significant effects on working conditions. [Continue reading in the article]